2014
DOI: 10.11646/zootaxa.3765.5.5
|View full text |Cite
|
Sign up to set email alerts
|

A new species of the genus Rhabdophis Fitzinger, 1843 (Squamata: Colubridae) from Guangdong Province, southern China

Abstract: A new species, Rhabdophis guangdongensis sp. nov., is described from the Guangdong Province, China. It can be easily distinguished from other known congeners by cyt b and c-mos sequences, and by the following combination of morphological characters: body size small; head distinct from the neck; 20 maxillary teeth, the three most posterior teeth strongly enlarged, and not separated by diastemata from other teeth; six supralabials, the third and fourth touching the eye; seven infralabials, the first four in cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…2). These phylogenetic results, combined with the distinctive coloration and morphological characteristics of these specimens, are consistent with the original description of R. guangdongensis (Zhu et al, 2014; see below), confirming the identity of these new specimens.…”
Section: Phylogenetic Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…2). These phylogenetic results, combined with the distinctive coloration and morphological characteristics of these specimens, are consistent with the original description of R. guangdongensis (Zhu et al, 2014; see below), confirming the identity of these new specimens.…”
Section: Phylogenetic Analysissupporting
confidence: 89%
“…The hemipenes were examined in one specimen (SICAU20160801-91). Identification of these five individuals was based on the description by Zhu et al (2014) and confirmed by our molecular analysis. Fresh liver tissue was collected from all specimens and immediately preserved in 95% ethanol.…”
Section: Samplingmentioning
confidence: 80%
See 1 more Smart Citation
“…(2014) Rhabdophis leonardi _1HT0851China LC325300 LC325747 LC326012 This study Rhabdophis leonardi*_ 2HT0852China LC325300 This study Rhabdophis leonardi*_ 3HT0853China LC325300 This study Rhabdophis leonardi _4RDQ200905367China KF800932 KF800922 Zhu et al. (2014) Rhabdophis murudensis HT0788Malaysia LC325341 LC325787 This study Rhabdophis nigrocinctus _1HT0253Thailand LC325307 LC325753 LC326015 This study Rhabdophis nigrocinctus _2HT0343Thailand …”
Section: Accession Numbers and Their Localities (Countries) For All Dmentioning
confidence: 97%
“…Rhabdophis guangdongensis was decribed by Zhu (Zhu et al 2014). Presently, Genus Rhabdophis, including 22 species, is widely distributed in East Asia and South Asia (http:// www.reptile-database.org/).…”
mentioning
confidence: 99%